GE_GERICHTE P/10256/2016 vom 4. September 2022 - GE Cour de justice (2022)
PRINCIPE DE L'ACCUSATION;LÉSION CORPORELLE SIMPLE;MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);ENLÈVEMENT(INFRACTION);CONTRAINTE SEXUELLE;VIOL;MESURE THÉRAPEUTIQUE INSTITUTIONNELLE;EXPULSION(DROIT PÉNAL) | CP.123.ch1; CP.123.al5.ch2; CP.180.al1; CP.181; CP.183; CP.190; CP.189; CP.59; CP.66a.al1; CPP.9